Microglia activation in central nervous system disorders: A review of recent mechanistic investigations and development efforts - Qin, Jun; Ma, Zhihui; Chen, Xiaoli; Shu, Shiyu (Frontiers in Neurology, 2023)
Abstract: Microglia (MG) are the main immune cells in the central nervous system (CNS). They are the primary line of defense in the brain's innate immune response to infection, injury, and disease. In recent years, MG activation has become a research hotspot for many diseases, including CNS diseases. Activation of MG leads to CNS inflammatory responses that play important roles in the occurrence and development of many neurological diseases such as Parkinson's disease, Alzheimer's disease, spinal cord injury, and brain injury. With changes in the local microenvironment, the phenotype and function of MG change, leading to effects that favor or suppress inflammation, and this has corresponding disease effects. Identifying and blocking the signaling pathways involved in MG activation may provide new prospects for better prevention and treatment of neurological diseases.